Preparation method and application of para-aramid pulp

By adding co-solvents and catalysts to amide solvents, precipitation forms para-aramid pulp with high specific surface area, solving the problems of high preparation cost and complex process in the prior art, achieving high Strong and low cost material preparation.

CN119265991APending Publication Date: 2025-01-07JIANGSU SHENGBANG NEW MATERIALS CO LTD

Patent Information

Application Number
CN202411391036.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing para-aramid pulp preparation technology cannot meet the needs of high tear strength, and the process is complex and costly. In particular, concentrated sulfuric acid solution leads to serious corrosion in the equipment and excessive investment costs.

Method used

Add co-solvents, solubilizers and catalysts to amide solvents to form para-aramid pulp with high specific surface area through precipitation and shearing, eliminating processes such as spinning, cutting and slurrying, and reducing production costs. Avoid strongly corrosive media.

Benefits of technology

The preparation of para-aramid pulp is achieved with high specific surface area, suitable for wet papermaking and high-performance reinforced materials, significantly improving the strength and tearing performance of the material, and the process is simple and cost-effective.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265991A_ABST
    Figure CN119265991A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of para-aramid pulp, and the preparation method comprises the following steps: (1) mixing para-aramid resin with a first amide solvent, a cosolvent, a solubilizer and a catalyst to obtain a para-aramid polymer solution; and (2) mixing the para-aramid high polymer solution obtained in the step (1) with a precipitation agent, and carrying out precipitation, shearing and cooling molding to obtain the para-aramid pulp. The preparation method provided by the invention is simple in process flow and low in investment cost, and the obtained para-aramid pulp has the advantages of high specific surface area, good morphology and the like, can be applied to the field of high-performance reinforcing materials such as aramid paper and the like, and remarkably improves the strength and tearing property of the materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of synthetic fibers, and in particular to a preparation method of para-aramid pulp and application thereof. Background Art

[0002] Para-aramid, or poly(p-phenylene terephthalamide) (PPTA), also known as aramid 1414, has the characteristics of high strength and modulus, light weight, flame retardancy, high temperature resistance, acid and alkali resistance, and good electrical insulation. Para-aramid pulp is a differentiated product of PPTA. Its chemical structure is the same as PPTA, and it retains the excellent properties of PPTA, such as high tensile strength, heat resistance, wear resistance, and dimensional stability. Aramid pulp has a rich microfibrillated structure, a certain aspect ratio, a large specific surface area, and a high amino content on the pulp surface, which helps to form hydrogen bonds with the resin matrix and enhance the composite effect. The good toughness, dispersibility, mixing, processability, and excellent composite properties of aramid pulp with other materials make it not only a raw material for aramid paper, but also widely used in sealing materials, reinforcing materials, friction materials, and other fields.

[0003] Para-aramid paper is made by wet papermaking process after para-aramid fiber and para-aramid pulp are made into pulp in a certain proportion. It has the characteristics of light specific gravity, high specific strength, high specific stiffness, high temperature resistance, etc., and is widely used in high-temperature insulation materials, aerospace, and high-performance electronic equipment. Para-aramid pulp fiber is crucial to the formation and quality of para-aramid paper. Compared with meta-aramid paper, para-aramid paper for honeycomb has higher requirements in terms of strength, high temperature resistance, etc. To improve the tear strength of para-aramid paper, it is necessary to increase the bonding force between the two fibers, and the bonding force between the fibers is mainly provided by para-aramid pulp, which requires para-aramid pulp to have a sufficiently high specific surface area. In the prior art, the highest specific surface area index of para-aramid pulp is 14m 2 / g; however, according to relevant industry experience, to produce para-aramid paper with high tear strength, the specific surface area of ​​para-aramid pulp must be at least 20m 2 / g, the currently available para-aramid pulp still cannot meet the demand for high tear strength.

[0004] With the development of the application of para-aramid pulp fiber, the requirements for its preparation technology are getting higher and higher. At present, one of the preparation technologies of para-aramid pulp is concentrated sulfuric acid solution liquid crystal spinning, cutting, and mechanical refining. For example, CN102535223A and CN104594094A both prepare para-aramid pulp by cutting and mechanical refining para-aramid filaments. The para-aramid pulp prepared by this method has too low specific surface area, resulting in too low cohesion between fibers, which is not suitable for the preparation of wet aramid paper. In addition, concentrated sulfuric acid seriously corrodes the equipment and the processing technology is complicated, resulting in high cost.

[0005] Another preparation technology of para-aramid pulp is precipitation method. For example, CN1475514A dissolves aramid 1414 resin with a certain characteristic viscosity in concentrated sulfuric acid to make a slurry, then adds it to a coagulation bath, and directly precipitates it after intense stirring to obtain para-aramid pulp. Due to the use of concentrated sulfuric acid, this process will cause serious corrosion to the equipment, and the equipment investment cost is too high, which leads to excessively high industrial production costs and low practicality. For another example, CN112375216A uses p-phenylenediamine and terephthaloyl chloride as reaction monomers, utilizes a low-temperature solution polycondensation method, gradually adds terephthaloyl chloride to carry out a polycondensation reaction, and assists with a solubilizer and an acid absorbent to promote the polycondensation reaction to obtain a poly(p-phenylene terephthalamide) product with a relatively high molecular weight, and further passes through a coagulation liquid to precipitate into fibers to obtain para-aramid pulp. The para-aramid pulp obtained by this method has a molecular weight of less than 8m 2 / g, which is not suitable for the manufacture of wet-laid aramid paper, and the unit product cost is also high.

[0006] Therefore, how to provide a method for preparing high specific surface area para-aramid pulp which is suitable for wet papermaking and has simple process and low cost has become a problem to be solved urgently. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides a method for preparing para-aramid pulp and its application, wherein para-aramid resin is dissolved in an amide solvent in the presence of a cosolvent, a solubilizer and a catalyst, and precipitated into fibers, thereby obtaining para-aramid pulp with a high specific surface area suitable for wet papermaking. The method of the present invention has a simple process flow and low investment cost. By adjusting the process parameters, para-aramid pulp with stable performance and size can be obtained, which can be applied to the field of high-performance reinforcing materials such as aramid paper and composite materials, and significantly improves the strength and tearing properties of the material.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing para-aramid pulp, the preparation method comprising the following steps:

[0010] (1) mixing a para-aramid resin with a first amide solvent, a co-solvent, a solubilizing agent and a catalyst to obtain a para-aramid polymer solution;

[0011] (2) The para-aramid polymer solution obtained in step (1) is mixed with a precipitating agent, precipitated, sheared, cooled and formed to obtain the para-aramid pulp.

[0012] The para-aramid pulp preparation method provided by the present invention adds a catalyst that plays a catalytic acceleration role on the co-solvent and the solubilizing agent, so that the co-solvent, the solubilizing agent and the catalyst are synergistically enhanced, the solubility of the para-aramid resin in the polar amide solvent is improved, and a para-aramid polymer solution with a high solid content is obtained. After mixing with a precipitating agent, a mass of para-aramid pulp is formed by high-speed shearing through a precipitating device, and then further cooled and formed to obtain a para-aramid pulp finished product with a high specific surface area. The present invention directly uses PPTA solution to prepare pulp, omitting the spinning, cutting, refining and other processes of the traditional process, reducing the production cost, and the whole production process does not have a highly corrosive medium, which greatly reduces the equipment investment cost. The para-aramid pulp prepared by the method has a high degree of fibrillation, good dispersibility, uniform morphology and rich hairiness, and is suitable for preparing high-performance reinforcing materials such as aramid paper and composite materials.

[0013] Preferably, the intrinsic viscosity of the para-aramid resin is 1.3-1.9 dL / g, for example, 1.35 dL / g, 1.4 dL / g, 1.5 dL / g, 1.6 dL / g, 1.7 dL / g or 1.8 dL / g.

[0014] In the present invention, the intrinsic viscosity (the reduced viscosity when the concentration of the polymer solution approaches zero) is obtained by referring to GB / T3401-2007 test.

[0015] Preferably, the mass concentration of the para-aramid resin in the para-aramid polymer solution is 8-16%, for example, 9%, 10%, 12%, 14% or 15%.

[0016] In the present invention, the para-aramid resin concentration used is too low or too high, which will affect the para-aramid pulp molding. If the resin concentration is too low, it cannot be completely precipitated due to the high solvent concentration, resulting in incomplete para-aramid pulp molding and the formation of pulp lumps; if the resin concentration is too high, it precipitates too quickly due to the low solvent concentration, resulting in the para-aramid polymer solidifying into lumps before fibrillation.

[0017] Preferably, the first amide solvent includes any one of N,N-dimethylacetamide, N-methylpyrrolidone or N-acetylpyrrolidone, or a combination of at least two thereof.

[0018] Preferably, the water content of the first amide solvent is ≤120 ppm, for example, it may be 115 ppm, 110 ppm, 105 ppm, 100 ppm, 90 ppm, 80 ppm, 60 ppm, 40 ppm or 20 ppm.

[0019] Preferably, the co-solvent comprises a chloride salt.

[0020] Preferably, the co-solvent includes any one of calcium chloride, lithium chloride or aluminum chloride, or a combination of at least two of them.

[0021] Preferably, the mass of the co-solvent is 1-5% of the mass of the first amide solvent, for example, it can be 1.5%, 2%, 2.5%, 3%, 3.5%, 4% or 4.5%.

[0022] Preferably, the solubilizer includes any one of polyvinyl pyrrolidone, alkylphenol polyoxyethylene ether, alkyl polyoxyethylene polyoxypropylene ether or fatty alcohol polyoxyethylene ether, or a combination of at least two thereof.

[0023] Preferably, the content of the solubilizer in the para-aramid polymer solution is 5-10 g / L, for example, 5.5 g / L, 6 g / L, 6.5 g / L, 7 g / L, 8 g / L or 9 g / L.

[0024] Preferably, the catalyst comprises a Lewis acid catalyst.

[0025] Preferably, the catalyst comprises any one of aluminum trichloride, boron trifluoride, ferric trichloride or ferric bromide, or a combination of at least two thereof.

[0026] Preferably, the content of the catalyst in the para-aramid polymer solution is 2-5 g / L, for example, 2.5 g / L, 3 g / L, 3.5 g / L, 4 g / L or 4.5 g / L.

[0027] Preferably, the mixing in step (1) comprises: mixing the first amide solvent and the co-solvent to obtain a solvent system, and then dissolving the para-aramid resin, the solubilizer and the catalyst in the solvent system to obtain the para-aramid polymer solution.

[0028] Preferably, the mixing is performed in the first PPTA solution preparation tank and / or the second PPTA solution preparation tank.

[0029] As a preferred technical solution of the present invention, during the production process, the first blending tank and the second blending tank alternately blend materials to ensure that the production can be carried out continuously and stably.

[0030] Preferably, the mass ratio of the para-aramid polymer solution to the precipitating agent is 1:(1-10), wherein the specific value of (1-10) can be, for example, 2, 3, 4, 5, 6, 7, 8 or 9.

[0031] In the present invention, when the ratio of the precipitating agent to the para-aramid polymer solution is 1:(1-10), the product pulp can be better formed. The higher the solvent content in the precipitating agent, the slower the polymer precipitation speed in the para-aramid polymer solution; the higher the proportion of the precipitating agent with the same solvent content relative to the para-aramid polymer solution during precipitation, the faster the polymer precipitation speed in the para-aramid polymer solution, and vice versa; when the mass ratio of the para-aramid polymer solution to the precipitating agent is lower than 1:1, the polymer in the para-aramid polymer solution is not completely precipitated and pulp cannot be formed; when the mass ratio of the para-aramid polymer solution to the precipitating agent is higher than 1:10, the polymer in the para-aramid polymer solution precipitates too quickly, causing the para-aramid polymer to solidify into a mass before fibrillation, and pulp cannot be formed.

[0032] Preferably, the precipitating agent comprises a combination of water and a second amide solvent.

[0033] Preferably, the second amide solvent includes any one of N,N-dimethylacetamide, N-methylpyrrolidone or N-acetylpyrrolidone, or a combination of at least two thereof.

[0034] Preferably, the composition of the second amide solvent is the same as that of the first amide solvent.

[0035] Preferably, the mass content of the second amide solvent in the precipitating agent is 30-70%, for example, 35%, 40%, 45%, 50%, 55%, 60% or 65%.

[0036] Preferably, the electrical conductivity of the water is less than 10 μs / cm, for example, it may be 9 μs / cm, 8 μs / cm, 6 μs / cm, 4 μs / cm or 2 μs / cm.

[0037] Preferably, the total amount of iron in the water is ≤50 μg / L, for example, it can be 45 μg / L, 40 μg / L, 35 μg / L, 30 μg / L, 25 μg / L, 20 μg / L or 10 μg / L.

[0038] Preferably, the hardness of the water, calculated as CaCO3, is ≤2 μmol / L, for example, it may be 1.8 μmol / L, 1.6 μmol / L, 1.4 μmol / L, 1.2 μmol / L, 1 μmol / L or 0.5 μmol / L, etc.

[0039] Preferably, the pH value of the water is 7-7.5, for example, it may be 7.05, 7.1, 7.2, 7.3 or 7.4.

[0040] Preferably, the precipitating agent is prepared in a first precipitating agent preparation tank and / or a second precipitating agent preparation tank.

[0041] As a preferred technical solution of the present invention, during the production process, the first precipitant preparation tank and the second precipitant preparation tank flow alternately prepare materials to ensure that the production can be carried out continuously and stably.

[0042] Preferably, the precipitation and shearing are carried out in a precipitator.

[0043] Preferably, the feeding temperature of the para-aramid polymer solution and the precipitating agent is independently 0-20°C, for example, 2°C, 5°C, 8°C, 10°C, 12°C, 15°C or 18°C.

[0044] As a preferred technical solution of the present invention, the PPTA solution and the precipitating agent are transported to the precipitation equipment at a stable low temperature, and the PPTA solution is coagulated under the high-speed shearing action of the precipitation equipment to form a para-aramid pulp with fine fiber clusters rich in hairiness. The obtained precipitated fibers have good dispersibility and rich morphological hairiness.

[0045] Preferably, the feed flow rate of the para-aramid polymer solution is 100-500 kg / h, for example, 150 kg / h, 200 kg / h, 250 kg / h, 300 kg / h, 350 kg / h, 400 kg / h or 450 kg / h.

[0046] Preferably, the feed flow rate of the precipitating agent is 100-5000 kg / h, for example, it can be 200 kg / h, 500 kg / h, 1000 kg / h, 1500 kg / h, 2000 kg / h, 3000 kg / h or 4000 kg / h.

[0047] Preferably, the shearing rotation speed is 800-4000 rpm, for example, it can be 1000 rpm, 1500 rpm, 2000 rpm, 2500 rpm, 3000 rpm or 3500 rpm.

[0048] Preferably, the cooling and forming is carried out in a storage tank.

[0049] Preferably, the cooling molding temperature is 10-30°C, for example, it can be 12°C, 15°C, 18°C, 20°C, 22°C, 25°C or 28°C.

[0050] As a preferred technical solution of the present invention, during the production process, cooling and forming are carried out alternately in the first storage tank and the second storage tank to ensure continuous and stable production operation.

[0051] Preferably, the cooling and molding is followed by post-processing to obtain the para-aramid pulp.

[0052] Preferably, the post-treatment includes filtering, washing and drying.

[0053] Preferably, the washing comprises continuous reverse water washing.

[0054] As a preferred technical solution of the present invention, continuous reverse water washing is adopted to save water costs and ensure continuous operation of the production process.

[0055] Preferably, the liquid content in the para-aramid pulp is less than 0.05%, for example, it may be 0.04%, 0.03%, 0.02%, 0.01% or 0.005%.

[0056] As a preferred technical solution of the present invention, the post-treatment comprises the following steps: the mixture containing solvent obtained by cooling and molding passes through two continuous filtering and washing machines, first filtering out the solvent, and then washing with washing water, the washing water added to the second continuous filtering and washing machine is desalted water; the solvent obtained by filtration is sent to a solvent recovery system, and reused after treatment; the washed para-aramid pulp passes through a continuous dryer to remove moisture, and finally enters a continuous packaging machine to complete packaging, thereby obtaining the para-aramid pulp with a high specific surface area;

[0057] The conductivity of the desalted water is less than 10 μs / cm, the total amount of iron is ≤50 μg / L, the hardness is ≤2 μmol / L in terms of CaCO3, and the pH value is 7-7.5.

[0058] In a second aspect, the present invention provides a para-aramid pulp, wherein the para-aramid pulp is prepared by the preparation method described in the first aspect.

[0059] Preferably, the specific surface area of ​​the para-aramid pulp is 22-36 m 2 / g, for example, 24m 2 / g, 26m 2 / g, 28m 2 / g, 30m 2 / g, 32m 2 / g or 34m 2 / g, etc.

[0060] Preferably, the length of the para-aramid pulp is 1.5-4 mm, for example, 1.8 mm, 2 mm, 2.5 mm, 3 mm or 3.5 mm.

[0061] Preferably, the density of the para-aramid pulp is 1.3-1.5 g / cm 3 , for example, 1.32 g / cm 3 , 1.35g / cm 3 , 1.38g / cm 3 , 1.4g / cm 3 , 1.42g / cm 3 , 1.45g / cm3 or 1.48 g / cm 3 wait.

[0062] The preparation method of para-aramid pulp provided by the invention can be used to produce various para-aramid pulp products with stable dimensions by adjusting parameters such as the concentration and temperature of PPTA solution, the concentration and temperature of precipitating agent, and the shear rate of precipitator.

[0063] In a third aspect, the present invention provides a use of the para-aramid pulp as described in the second aspect in a reinforcing material.

[0064] Compared with the prior art, the present invention has at least the following beneficial effects:

[0065] The present invention provides a preparation method and application of para-aramid pulp. A cosolvent, a solubilizing agent and a catalyst are added to an amide solvent to improve the solubility of PPTA, thereby obtaining a para-aramid polymer solution with a high solid content. The para-aramid polymer solution and a precipitating agent are solidified under the high-speed shearing action of a precipitating device to form fine fibrous para-aramid pulp with rich hairiness, and the finished product can be obtained by cooling, molding, washing and removing the solvent. The overall process is simple and effective, and continuous production can be realized, with low unit product production cost and equipment investment cost. The obtained para-aramid pulp has the advantages of high specific surface area, good morphology and the like, and can meet the preparation requirements of high tear strength materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] Figure 1 It is a schematic diagram of the process of preparing para-aramid pulp in Example 1. DETAILED DESCRIPTION

[0067] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0068] In the following specific implementation of the present invention, the materials involved are as follows:

[0069] (1) Solubilizer

[0070] Polyvinyl pyrrolidone, Boai New Open Source Medical Technology Group Co., Ltd., K30.

[0071] (2) Solvent

[0072] Calcium chloride, Shandong Tianjian Water Treatment Technology Co., Ltd., spherical particles.

[0073] In the following examples and comparative examples, the specific surface area of ​​the obtained para-aramid pulp was measured with reference to GB / T19587-2017, and the fiber length was measured with reference to TAPPI T271.

[0074] Example 1

[0075] A method for preparing para-aramid pulp, the process diagram of the preparation method is as follows Figure 1 As shown, the following steps are included:

[0076] (1) Under the protection of dry nitrogen, first add N,N-dimethylacetamide (DMAC) into PPTA solution preparation tank A / B, then add co-solvent calcium chloride to make its mass fraction 2%, stir evenly, then dissolve PPTA resin with an intrinsic viscosity of 1.4 dL / g in the DMAC solvent system to make its mass fraction 8%, and at the same time add 5g / L solubilizer polyvinyl pyrrolidone and 2g / L catalyst aluminum chloride, stir evenly to obtain para-aramid polymer solution, and cool to 15°C for use.

[0077] (2) Add desalted water and DMAC into the precipitant preparation tank A / B and stir evenly to obtain a precipitant with a DMAC content of 35%, and cool to 5° C. for use.

[0078] (3) The para-aramid polymer solution and precipitant obtained in step (1) are continuously and stably introduced into a precipitator at flow rates of 200 kg / h and 1600 kg / h, respectively, and pulp is formed by high-speed shearing at 1000 rpm in the precipitator. The obtained material is discharged into a storage tank A / B for further cooling and forming. The cooling temperature is controlled at 20° C. to obtain a mixed material containing a solvent.

[0079] (4) The solvent-containing mixture obtained in step (3) is passed through two continuous filtering and washing machines to first filter out the solvent and then wash with washing water, wherein the washing water added to the second continuous filtering and washing machine is desalted water; the solvent is filtered out and sent to a solvent recovery system, and the recovered solvent is reused; the cleaned para-aramid pulp is continuously dried to remove the liquid component to obtain a finished para-aramid pulp product.

[0080] The obtained para-aramid pulp was light yellow in color. After adding water, it was observed to be flocculent and translucent fiber clusters with an average specific surface area of ​​22.7 m 2 / g, and the average fiber length is 2.1mm.

[0081] Example 2

[0082] A method for preparing para-aramid pulp, the method comprising the following steps:

[0083] (1) Under the protection of dry nitrogen, first add N,N-dimethylacetamide (DMAC) into PPTA solution preparation tank A / B, then add co-solvent calcium chloride to make its mass fraction 3%, stir evenly, then dissolve PPTA resin with an intrinsic viscosity of 1.5 dL / g in the DMAC solvent system to make its mass fraction 8%, and at the same time add 6g / L solubilizer polyvinyl pyrrolidone and 4g / L catalyst ferric bromide, stir evenly to obtain a para-aramid polymer solution, and cool to 15°C for use.

[0084] (2) Add desalted water and DMAC into the precipitant preparation tank A / B and stir evenly to obtain a precipitant with a DMAC content of 45%, and cool to 10° C. for standby use.

[0085] (3) The para-aramid polymer solution and precipitant obtained in step (1) are continuously and stably introduced into a precipitator at flow rates of 200 kg / h and 1600 kg / h, respectively, and pulp is formed by high-speed shearing at 1500 rpm in the precipitator. The obtained material is discharged into a storage tank A / B for further cooling and forming. The cooling temperature is controlled at 20°C to obtain a mixed material containing a solvent.

[0086] (4) The solvent-containing mixture obtained in step (3) is passed through two continuous filtering and washing machines to first filter out the solvent and then wash with washing water, wherein the washing water added to the second continuous filtering and washing machine is desalted water; the solvent is filtered out and sent to a solvent recovery system, and the recovered solvent is reused; the cleaned para-aramid pulp is continuously dried to remove the liquid component to obtain a finished para-aramid pulp product.

[0087] The obtained para-aramid pulp was light yellow in color. After adding water, it was observed to be flocculent and translucent fiber clusters with an average specific surface area of ​​26.6 m 2 / g, and the average fiber length is 2.3mm.

[0088] Example 3

[0089] A method for preparing para-aramid pulp, the method comprising the following steps:

[0090] (1) Under the protection of dry nitrogen, first add N,N-dimethylacetamide (DMAC) into PPTA solution preparation tank A / B, then add co-solvent calcium chloride to make its mass fraction 4%, stir evenly, then dissolve PPTA resin with an intrinsic viscosity of 1.6 dL / g in the DMAC solvent system to make its mass fraction 14%, and at the same time add 7g / L solubilizer polyvinyl pyrrolidone and 3.5g / L catalyst ferric chloride, stir evenly to obtain a para-aramid polymer solution, and cool to 25°C for use.

[0091] (2) Add desalted water and DMAC into the precipitant preparation tank A / B and stir evenly to obtain a precipitant with a DMAC content of 50%, and cool to 15° C. for use.

[0092] (3) The para-aramid polymer solution and precipitant obtained in step (1) are continuously and stably introduced into a precipitator at flow rates of 200 kg / h and 800 kg / h, respectively, and pulp is formed by high-speed shearing at 1800 rpm in the precipitator. The obtained material is discharged into a storage tank A / B for further cooling and forming. The cooling temperature is controlled at 20°C to obtain a mixed material containing a solvent.

[0093] (4) The solvent-containing mixture obtained in step (3) is passed through two continuous filtering and washing machines to first filter out the solvent and then wash with washing water, wherein the washing water added to the second continuous filtering and washing machine is desalted water; the solvent is filtered out and sent to a solvent recovery system, and the recovered solvent is reused; the cleaned para-aramid pulp is continuously dried to remove the liquid component to obtain a finished para-aramid pulp product.

[0094] The obtained para-aramid pulp was light yellow in color. After adding water, it was observed to be flocculent and translucent fiber clusters with an average specific surface area of ​​33.2 m 2 / g, and the average fiber length is 2.5mm.

[0095] Example 4

[0096] A method for preparing para-aramid pulp, the method comprising the following steps:

[0097] (1) Under the protection of dry nitrogen, N,N-dimethylacetamide (DMAC) was first added to the PPTA solution preparation tank A / B, and then the co-solvent calcium chloride was added to make its mass fraction 5%, and stirred evenly. Then, the PPTA resin with an intrinsic viscosity of 1.7 dL / g was dissolved in the DMAC solvent system to make its mass fraction 14%, and 8 g / L of solubilizer polyvinyl pyrrolidone and 5 g / L of catalyst boron trifluoride were added at the same time, and stirred evenly to obtain a para-aramid polymer solution, which was cooled to 25°C for use.

[0098] (2) Add desalted water and DMAC into the precipitant preparation tank A / B and stir evenly to obtain a precipitant with a DMAC content of 65%, and cool to 15° C. for use.

[0099] (3) The para-aramid polymer solution and precipitant obtained in step (1) are continuously and stably introduced into a precipitator at flow rates of 200 kg / h and 1000 kg / h, respectively, and pulp is formed by high-speed shearing at 1800 rpm in the precipitator. The obtained material is discharged into a storage tank A / B for further cooling and forming. The cooling temperature is controlled at 20° C. to obtain a mixture containing a solvent.

[0100] (4) The solvent-containing mixture obtained in step (3) is passed through two continuous filtering and washing machines to first filter out the solvent and then wash with washing water, wherein the washing water added to the second continuous filtering and washing machine is desalted water; the solvent is filtered out and sent to a solvent recovery system, and the recovered solvent is reused; the cleaned para-aramid pulp is continuously dried to remove the liquid component to obtain a finished para-aramid pulp product.

[0101] The obtained para-aramid pulp was light yellow in color. After adding water, it was observed to be flocculent and translucent fiber clusters with an average specific surface area of ​​29.4 m 2 / g, and the average fiber length is 2.6mm.

[0102] Example 5

[0103] A method for preparing para-aramid pulp, the preparation method differing from Example 1 only in that in step (1), PPTA resin is dissolved in a DMAC solvent system to a mass fraction of 19%, and other materials, amounts, and preparation methods are the same as those in Example 1.

[0104] The obtained para-aramid pulp is light yellow, irregular in size, smooth on the surface, and has an average specific surface area of ​​2.4 m 2 / g.

[0105] Example 6

[0106] A method for preparing para-aramid pulp, the preparation method differing from Example 1 only in that in step (3), the para-aramid polymer solution and precipitant obtained in step (1) are continuously and stably introduced into a precipitator at flow rates of 1000kg / h and 700kg / h, respectively, and other materials, amounts, and preparation methods are the same as those in Example 1.

[0107] The obtained para-aramid pulp is light yellow, irregular in size, smooth on the surface, and has an average specific surface area of ​​3.3 m 2 / g.

[0108] Example 7

[0109] A method for preparing para-aramid pulp, the preparation method differing from Example 1 only in that in step (3), the para-aramid polymer solution and precipitant obtained in step (1) are continuously and stably introduced into a precipitator at flow rates of 150kg / h and 1650kg / h, respectively, and other materials, amounts, and preparation methods are the same as those in Example 1.

[0110] The obtained para-aramid pulp is light yellow, with irregular lengths of flocculent fine fibers and an average specific surface area of ​​19.1 m 2 / g, and the average fiber length is 0.13mm.

[0111] Example 8

[0112] A method for preparing para-aramid pulp, the preparation method differs from Example 1 only in that in step (2), the mass content of DMAC in the precipitating agent is adjusted to 25%, and other materials, dosages, and preparation methods are the same as those in Example 1.

[0113] The obtained para-aramid pulp is light yellow, irregular in size, smooth on the surface, and has an average specific surface area of ​​4.2 m 2 / g.

[0114] Example 9

[0115] A method for preparing para-aramid pulp, the preparation method differs from Example 4 only in that in step (2), the mass content of DMAC in the precipitating agent is adjusted to 75%, and other materials, amounts, and preparation methods are the same as those in Example 4.

[0116] The obtained para-aramid pulp is light yellow, irregular in size, smooth on the surface, and has an average specific surface area of ​​2.2 m 2 / g.

[0117] Comparative Example 1

[0118] A method for preparing para-aramid pulp, the method comprising the following steps:

[0119] Under the protection of dry nitrogen, N, N-dimethylacetamide (DMAC) was first added to the PPTA solution preparation tank A / B, and then the co-solvent calcium chloride was added to make its mass fraction 5%, and stirred evenly, and then the PPTA resin with an intrinsic viscosity of 1.7dL / g was dissolved in the DMAC solvent system, and 8g / L of solubilizer polyvinyl pyrrolidone was added at the same time, without adding a catalyst, and stirred evenly to obtain a para-aramid polymer solution, which was cooled to 25°C for use, and the mass fraction of the obtained para-aramid polymer solution was 6.5%.

[0120] (2) Add desalted water and DMAC into the precipitant preparation tank A / B and stir evenly to obtain a precipitant with a DMAC content of 65%, and cool to 15° C. for use.

[0121] (3) The para-aramid polymer solution and precipitant obtained in step (1) are continuously and stably introduced into a precipitator at flow rates of 200 kg / h and 1000 kg / h, respectively, and pulp is formed by high-speed shearing at 1800 rpm in the precipitator. The obtained material is discharged into a storage tank A / B for further cooling and forming. The cooling temperature is controlled at 20° C. to obtain a mixture containing a solvent.

[0122] (4) The solvent-containing mixture obtained in step (3) is passed through two continuous filtering and washing machines to first filter out the solvent and then wash with washing water, wherein the washing water added to the second continuous filtering and washing machine is desalted water; the solvent is filtered out and sent to a solvent recovery system, and the recovered solvent is reused; the cleaned para-aramid pulp is continuously dried to remove the liquid component to obtain a finished para-aramid pulp product.

[0123] The obtained para-aramid pulp is light yellow irregular long and short flocculent fine fibers with an average specific surface area of ​​17.3m 2 / g, and the average fiber length is 0.15mm, which does not meet the product requirements.

[0124] The test results show that the para-aramid pulp preparation method provided by the present invention adopts a combination of a cosolvent, a solubilizer and a catalyst to synergistically improve the solubility of PPTA in an amide solvent to obtain a para-aramid polymer solution with a high solid content, which is then coagulated with a precipitant under the high-speed shearing action of a precipitator to form a clumping para-aramid pulp with rich hairiness, and the specific surface area can reach 22.7 m 2 / g or more, the larger the specific surface area of ​​para-aramid pulp, the stronger the cohesion between fibers, and the more suitable it is for the preparation of high-performance materials such as aramid paper. The preparation method provided by the present invention has simple steps, can realize continuous production, and has low comprehensive costs such as unit product production cost and equipment investment cost, which is conducive to large-scale industrial production.

[0125] By comparing Example 1 with Example 5, it can be seen that the present invention obtains a pulp product with better effect by limiting the mass concentration of para-aramid resin in the para-aramid polymer solution. The reason is that the solid content of the para-aramid polymer solution is too high, and the solvent inside the pulp mass cannot be precipitated in time during production, while the surface of the pulp mass has solidified.

[0126] By comparing Example 1 with Examples 6 and 7, it can be seen that the present invention improves the product morphology by using a specific ratio of precipitating agent and para-aramid polymer solution for precipitation. When the amount of precipitating agent added is insufficient, the solvent inside the slurry cannot be precipitated out in time and evenly, and the polymer instantly solidifies into a mass during water washing, and a mass-like fiber structure cannot be formed; when the amount of precipitating agent added is too large, the surface of the para-aramid polymer slurry mass solidifies rapidly, the solvent inside the slurry mass cannot be precipitated out in time and evenly, and a mass-like fiber structure cannot be formed.

[0127] By comparing Examples 1 and 4 with Examples 8 and 9, it can be seen that the present invention improves the product morphology by using a precipitant having a specific amide solvent content and a para-aramid polymer solution for precipitation. When the DMAC content in the precipitant is insufficient, the para-aramid polymer solution is excessively dispersed in the precipitant, and the polymer instantly solidifies into a mass during water washing, and a mass-like fiber structure cannot be formed; when the DMAC content in the precipitant is too high, the surface of the para-aramid polymer slurry mass solidifies rapidly, the solvent inside the slurry mass cannot be precipitated in time and evenly, and a mass-like fiber structure cannot be formed.

[0128] By comparing Example 4 with Comparative Example 1, it can be seen that a pulp product that meets the requirements cannot be obtained in the absence of a catalyst. This is because without adding a catalyst, the mass fraction of the obtained para-aramid polymer solution is too small, resulting in excessive dispersion of the para-aramid polymer solution in the precipitant and failure to form a clumping structure. In addition, the obtained pulp has a small specific surface area and is difficult to meet the application requirements of high-performance materials.

[0129] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing para-aramid pulp, characterized in that: The preparation method comprises the following steps: (1) mixing a para-aramid resin with a first amide solvent, a co-solvent, a solubilizing agent and a catalyst to obtain a para-aramid polymer solution; (2) The para-aramid polymer solution obtained in step (1) is mixed with a precipitating agent, precipitated, sheared, cooled and formed to obtain the para-aramid pulp.

2. The preparation method according to claim 1, characterized in that: The intrinsic viscosity of the para-aramid resin is 1.3-1.9 dL / g; Preferably, the mass concentration of the para-aramid resin in the para-aramid polymer solution is 8-16%; Preferably, the first amide solvent includes any one of N,N-dimethylacetamide, N-methylpyrrolidone or N-acetylpyrrolidone, or a combination of at least two thereof; Preferably, the water content of the first amide solvent is ≤120 ppm.

3. The preparation method according to claim 1 or 2, characterized in that: The co-solvent comprises a chloride salt; Preferably, the co-solvent comprises any one or a combination of at least two of calcium chloride, lithium chloride or aluminum chloride; Preferably, the mass of the co-solvent is 1-5% of the mass of the first amide solvent; Preferably, the solubilizer comprises any one of polyvinyl pyrrolidone, alkylphenol polyoxyethylene ether, alkyl polyoxyethylene polyoxypropylene ether or fatty alcohol polyoxyethylene ether, or a combination of at least two thereof; Preferably, the content of the solubilizer in the para-aramid polymer solution is 5-10 g / L; Preferably, the catalyst comprises a Lewis acid catalyst; Preferably, the catalyst comprises any one or a combination of at least two of aluminum trichloride, boron trifluoride, ferric trichloride or ferric bromide; Preferably, the content of the catalyst in the para-aramid polymer solution is 2-5 g / L.

4. The preparation method according to any one of claims 1 to 3, characterized in that The mixing in step (1) comprises: mixing the first amide solvent and the co-solvent to obtain a solvent system, and then dissolving the para-aramid resin, the solubilizer and the catalyst in the solvent system to obtain the para-aramid polymer solution.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The mass ratio of the para-aramid polymer solution to the precipitating agent is 1:(1-10); Preferably, the precipitating agent comprises a combination of water and a second amide solvent; Preferably, the second amide solvent includes any one of N,N-dimethylacetamide, N-methylpyrrolidone or N-acetylpyrrolidone, or a combination of at least two thereof; Preferably, the composition of the second amide solvent is the same as that of the first amide solvent; Preferably, the mass content of the second amide solvent in the precipitating agent is 30-70%; Preferably, the electrical conductivity of the water is less than 10 μs / cm; Preferably, the total amount of iron in the water is ≤50 μg / L; Preferably, the hardness of the water is ≤2 μmol / L in terms of CaCO3; Preferably, the pH value of the water is 7-7.

5.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The precipitation and shearing are carried out in a precipitator; Preferably, the feeding temperatures of the para-aramid polymer solution and the precipitating agent are independently 0-20°C; Preferably, the feed flow rate of the para-aramid polymer solution is 100-500 kg / h; Preferably, the feed flow rate of the precipitating agent is 100-5000 kg / h; Preferably, the shearing speed is 800-4000 rpm; Preferably, the cooling and forming is carried out in a storage tank; Preferably, the cooling molding temperature is 10-30°C.

7. The preparation method according to any one of claims 1 to 6, characterized in that: After the cooling and forming, post-processing is performed to obtain the para-aramid pulp; Preferably, the post-treatment includes filtering, washing and drying; Preferably, the washing comprises continuous reverse water washing.

8. A para-aramid pulp, characterized in that: The para-aramid pulp is prepared by the preparation method according to any one of claims 1 to 7.

9. The para-aramid pulp according to claim 8, characterized in that: The specific surface area of ​​the para-aramid pulp is 22-36 m 2 / g; Preferably, the length of the para-aramid pulp is 1.5-4 mm; Preferably, the density of the para-aramid pulp is 1.3-1.5 g / cm 3 .

10. Use of the para-aramid pulp according to claim 8 or 9 in a reinforcing material.

Citation Information

Patent Citations

  • Method for preparing and grading contrapuntal aramid pulp

    CN102535223A

  • Method for continuously producing para-aramid pulp

    CN104594094A

  • preparation method of para Fanglun slurry cake

    CN1475514A

  • One-step preparation method of para aramid fibrids

    CN102560737A

  • Method for preparing poly(p-phenylene terephthalamide) PPTA fibrid

    CN109321998A

Cited By

  • Recycled aramid pulp with mechanical force induced brooming and preparation method thereof

    CN120700724A